Effect of Iodine Overdose on Thyroid Hyperplasia - Tala A. Abdul Wahab (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: study the relation between the effect of time (long time duration) with high concentration of iodine and study its effect on the activity of the thyroid gland (homonal and histological changes). Methodology: An experimental study was done on (30) albino rats (8 weeks of age) to know the effect of high concentration of iodine on the activity of the thyroid gland aiormonal and histological changes) related with time. The study last for six months for the period of I/2/2007 to 31/7/2007, the experiment was carried out in the research lab. of pathology deparment, College of Medicine, University of Baghdad. Results: The study shows changes in homonal levels of thyroid hormones (T3 & T4) and also histological changes in the diameter and numbers of thyroid follicles and increase in the numbers of active hot follicles and decrease in the numbers of inactive cold follicles. The hot follicles takes faint blue colour after using the toluiden blue dye to stain the thyroid tissue while the cold follicles takes deep dark blue colour in the thyroid gland section when using the same dye. Recommendations: Canying out such a study for long time duration (lyear or more), and to study the correlation between the experimental results and the behavior of the human, and study the effect of iodine in different concentrations in mixture with thyroxin hormone